Pain score evaluation in patients underwent hand surgery under WALANT compared to those under local or general anesthesia with tourniquet - Teuku Nanda Putra; Yanis, Melissa Abigail (Surgical Residency Program Syiah Kuala University, 2023)
Background: The Wide Awake Local Anesthesia No Tourniquet (WALANT) has been reported to offer simpler pre-surgical instruction and assessment, faster operating time, better surgical visualization, shorter hospital stay, fewer complications and side effects, lower cost, faster post-operative recovery time, better patient’s satisfaction, and less pain and discomfort. This study aims to review the pain score in hand surgery using the WALANT technique compared to local anesthesia or general anesthesia with a tourniquet. Methods: A comprehensive literature search was conducted in PubMed, Cochrane Library, and Google Scholar in March 2021. Eligible randomized-controlled trials (RCTs) and cohort studies compared injection time intra-operative or post-operative pain using Visual Analog Score (VAS) in WALANT and local anesthesia or general anesthesia with a tourniquet. Results: Five studies (3 RCTs and two cohorts) were included in this article, including 645 hand surgeries (376 carpal tunnel syndrome cases, 181 trigger finger cases, 42 cubital tunnel syndrome cases, 44 de Quervain’s disease cases, and two ganglion cyst cases). Three studies reported a significantly lower VAS in the WALANT group, while the other two reported a lower VAS in the WALANT group, but not statistically significant. Conclusion: WALANT is still a technique worth considering in hand surgery because of its superiority in minimizing intra-operative and post-operative pain.